Mechanisms of Ti3Al precipitation in hcp α-Ti. (15th June 2021) - Dear, Felicity F.; Kontis, Paraskevas; Gault, Baptiste; Ilavsky, Jan; Rugg, David; Dye, David
Graphical abstract: Abstract: Nucleation and growth of Ti 3 Al α 2 ordered domains in α -Ti–Al–X alloys were characterised using a combination of transmission electron microscopy, atom probe tomography and small angle X-ray scattering. Model alloys based on Ti–7Al (wt.%) and containing O, V and Mo were aged at 550 ∘ C for times up to 120d and the resulting precipitate dispersions were observed at intermediate points. Precipitates grew to around 30nm in size, with a volume fraction of 6–10% depending on tertiary solutes. Interstitial O was found to increase the equilibrium volume fraction of α 2, while V and Mo showed relatively little influence. Addition of any of the solutes in this study, but most prominently Mo, was found to increase nucleation density and decrease precipitate size and possibly coarsening rate. Coarsening can be described by the Lifshitz-Slyozov-Wagner model, suggesting a matrix diffusion-controlled coarsening mechanism (rather than control by interfacial coherency). Solutionising temperature was found to affect nucleation number density with an activation energy of E f = 1.5 ± 0.4  eV, supporting the hypothesis that vacancy concentration affects α 2 nucleation. The observation that all solutes increase nucleation number density is also consistent with a vacancy-controlled nucleation mechanism.